High density polyethylene and zirconium phosphate nanocomposites - Lino,Adan Santos (2015)
Abstract Nanocomposite based on high density polyethylene (HDPE) and layered zirconium phosphate organically modified with octadecylamine (ZrPOct) was obtained through melt processing. The ZrPOct was synthesized by precipitation and modified by suspension and sonication procedures. The initial and maximum degradation temperatures (Tonset and Tmax) were increased. A slight decrease of crystallinity degree was detected. Reduction of elastic modulus and elongation at break were noticed. The lamellar spacing was increased (3.3 times higher). The storage modulus decreased and low field nuclear magnetic resonance (LFNMR) revealed an increasing of molecular mobility. The presence of octadecylamine enhanced the entrance of HDPE in the ZrPOct galleries. Several characteristics of HDPE were changed indicating that intercalation was successful. All results indicated that partially intercalated and/or exfoliated nanocomposite was achieved.